Folksonomies to enhance the knowledge organization and management - Banek Zorica, Mihaela; Špiranec, Sonja; Ivanjko, Tomislav (2014)
The paper examines theoretical assumptions of the new models for knowledge organization in support of knowledge management.
Projekt MZOS
ENG